2021
DOI: 10.7759/cureus.12981
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Patients at Increased Risk of Developing Type II Endometrial Cancer: Relative and Absolute Risk Estimation and Implications for Counseling

Abstract: Introduction Breast cancer (BC) is a recognized risk factor for endometrial cancer (EC). Emerging literature indicates that it confers a higher risk of type II EC (T2EC) than type I EC (T1EC). Although some surgeons offer a prophylactic hysterectomy to BC patients referred for risk-reducing bilateral salpingo-oophorectomy, insufficient evidence prevents this from being the standard practice. We aimed to quantify their absolute risk and relative risk (RR) of developing both EC subtypes and identify a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…According to the inclusion criteria, in title/abstract and full text screening, 3960 and 35 studies were excluded, respectively. Finally, 26 studies were eligible for inclusion in meta‐analysis 11–14,20–41 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the inclusion criteria, in title/abstract and full text screening, 3960 and 35 studies were excluded, respectively. Finally, 26 studies were eligible for inclusion in meta‐analysis 11–14,20–41 …”
Section: Resultsmentioning
confidence: 99%
“…Finally, 26 studies were eligible for inclusion in meta‐analysis. 11 , 12 , 13 , 14 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Guo et al [8] showed that the incidence of EC was increased by 15-16 fold in BC patients. Portella et al [13] found that in BC patients the risk for type I and type II EC was 12.4-and 33.9-fold higher as compared to the general population, respectively. Gehrig et al [10] found a 2.6-fold increased risk for USC compared to endometroid EC in BC survivors.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated the association between BC and EC\USC [6,[8][9][10][11][12][13][14][15]. Guo et al [8] showed that the risk for EC after BC was approximately 15-16 times more than the general population in both estrogen receptor (ER)-positive and -negative BC subtypes.…”
Section: Introductionmentioning
confidence: 99%